Africa's Macroeconomic Story - Hostland, Douglas (World Bank, Washington, DC, 2014)
Much of Sub-Saharan Africa's post-independence macroeconomic history has been characterized by boom-bust cycles. Growth accelerations have been common, but short lived. Weak policy formulation and implementation led to large external and fiscal imbalances, excessive debt accumulation, volatile inflation, and sharp exchange rate fluctuations. This characterization changed, however, in the mid-1990s, when debt relief and better macroeconomic policy began to provide a source of stability that has helped sustain robust growth throughout much of the region. In resource rich countries, the process was supported over the past few years by a dramatic increase in commodity prices. But resources are only one part of the story. Growth has exhibited impressive resilience even in the face of negative external shocks, as in 2008-2009. While the short-term outlook remains positive, over the medium term policy makers face new challenges. Several countries have the potential to greatly expand natural resource production and become major commodity exporters; volatile resource revenue will complicate their fiscal and monetary planning. Rising investor appetite for financial assets of frontier markets and the development of domestic debt markets will continue to broaden the menu of and trade-offs among financing options at a time when global interest rates may start sloping upward. Complex financing arrangements -- notably for private-public or public-public partnerships in infrastructure -- will become more common and will generate new types of fiscal commitments and contingencies.